A computational framework to simulate the thermochemical process during thermochemical ablation of biological tissues. (June 2022) - Mak, Nguoy L.; Ooi, Ean H.; Lau, Ee V.; Ooi, Ean T.; Pamidi, N.; Foo, Ji J.; Mohd Ali, Ahmad F.
Abstract: Thermochemical ablation (TCA) is a thermal ablation therapy that utilises heat released from acid-base neutralisation reaction to destroy tumours. This procedure is a promising low-cost solution to existing thermal ablation treatments such as radiofrequency ablation (RFA) and microwave ablation (MWA). Studies have demonstrated that TCA can produce thermal damage that is on par with RFA and MWA when employed properly. Nevertheless, TCA remains a concept that is tested only in a few animal trials due to the risks involved as the result of uncontrolled infusion and incomplete acid-base reaction. In this study, a computational framework that simulates the thermochemical process of TCA is developed. The proposed framework consists of three physics, namely chemical flow, neutralisation reaction and heat transfer. An important parameter in the TCA framework is the neutralisation reaction rate constant, which has values in the order of 10 8  m 3 /(mol⋅s). The present study will demonstrate that since the rate constant impacts only the rate and direction of the reaction but has little influence on the extent of reaction, it is possible to replicate the thermochemical process of TCA by employing significantly smaller values of rate constant that are numerically tractable. Comparisons of the numerical results against experimental studies from the literature supports this. The aim of this framework is for researchers to advance and develop TCA to gain an in-depth understanding of the fundamental mechanisms of TCA and to develop a safe treatment protocol of TCA in the hope of advancing TCA into clinical trials. Graphical abstract: Image 1 Highlights: A computational framework that simulates thermochemical ablation (TCA) is proposed. The framework describes the thermochemical process during TCA of biological tissue. The framework adopts a small rate constant to describe acid-base neutralisation. Rate constant influences the rate and direction but not the extent of reaction. Predicted temperature rise matched well the experimental results from literature.